Parents’ perception towards the signs and symptoms of infant teething - Helena Maria Antunes Paiano; Denise Vizzotto; Célia Maria Condeixa de França Lopes; Dayane Ethur de Quadros; Gabriela Bittencourt Machado (Revista Sul-Brasileira de Odontologia, 2014)
The aim of this study was to evaluate the perception of parents or guardians about the signs and symptoms found during tooth eruption of their infants treated in the Pediatric Dentistry Clinics at the University of Joinville Region – Univille. Material and methods: We conducted an observational and crosssectional study using data collected from structured interviews with 50 parents and guardians. Results: Of the sample studied, only 18% said they had no knowledge on signs and symptoms of teething. Among the local events, itching/finger or object sucking was the most frequent (94%) followed by anxiety / irritability (86%). In open questions, the salivation increasing was found to be the most frequent response (36%) and 42 people employed some treatment to relieve the health alterations during teething. As regards to the attitudes taken, dentist appointment was reported by 11.63% of the people. Concerning to object sucking, 82% confirmed this behavior and 36.59% reported that these objects were cleaned. Of the respondents in this study, 43.90% would like to receive more information on this issue. Conclusion: Given these results, both the family and the health team must be oriented during the infants’ teething so that the prevalence of the signs and symptoms can be determined, known, and relieved.